Study of solid residues obtained from the pyrolysis of commercial plastic waste bottles by FTIR and TG methods - Gurbanov, Muslum Ahmed; Guliyeva, lviye Aydin; Mirzazada, Elshen Valeh (European Journal of Chemistry, 2025)
The composition of solid residues-products of thermal pyrolysis of plastic waste (polyethylene terephthalate (PET), polypropylene (PP)) at 350-550 °C was studied by Fourier transform infrared spectroscopy (FT-IR) and differential thermal analysis (DTA) methods. On the basis of the transition band (T%) the absorption and Abs parameters were calculated. It was observed that the Abs parameters of the peaks observed in the initial samples appear to change depending on the pyrolysis temperature, with the appearance of new peaks at higher temperatures. It was observed that during the pyrolysis of PET polymer waste, a number of bands with wavenumber 1692, 1670, 1262, 755, 694, and 464 cm-1 occurred at above 450 °C. It would seem that the Abs parameters for the 2923, 1453, and 846 cm-1 peaks observed in the initial samples are equal to zero. It would appear that during the pyrolysis of the PET polymer waste at 550 °C, only three peaks with wavenumbers of 1686, 1062 and 707 cm-1 are observed. Similarly, during the pyrolysis of the PP polymer waste at the same temperature, only one new peak (1092 cm-1) is observed. The solid residues of the pyrolysis processes for the samples taken at 550 °C are calculated and are equal to 13.6 and 0.6%, respectively, for PET and PP. The data shows that solid residues from the pyrolysis of PP wastes have a structure similar to that of charcoal.